An investigation into the integration of digital technology in teacher development for enhanced inclusion - Anderson, Meghan (School of Education, 2025)
The study addresses the problem of insufficient teacher training for technology integration in inclusive classrooms, and professional development opportunities. Prior research highlights barriers such as limited access, lack of confidence, and insufficient contextualised training, which hinder effective adoption. This research investigates the integration of digital technologies in teacher development to enhance inclusion within a South African all-girls school. It explores the intersection of digital tools, inclusive education practices, and teacher agency, employing Margaret Archer's theory of social realism. This study is significant in the context of growing demands for inclusive, technology-enabled education to address diverse learning needs. Using a design-based research approach, the research involved a case study, interviews, and surveys with teachers and subject heads to examine structural and cultural enablers and barriers, as well as teacher agency in using digital technologies. Data was collected over four phases, encompassing initial problem analysis, interventions, and the development of design principles. Findings reveal that structural factors such as infrastructure and training availability significantly impact technology adoption, while cultural factors like school norms and professional autonomy influence teachers' willingness to innovate. Teachers who exhibited higher agency adapted digital tools to create inclusive practices, leveraging technologies like interactive whiteboards and assistive tools to address diverse learner needs. The study contributes to understanding the interplay between structure, culture, and agency in educational contexts. It underscores the importance of targeted professional development and context-aware strategies to overcome barriers. The implications suggest that fostering teacher agency and integrating culturally relevant technologies are pivotal for advancing inclusive education. Future recommendations include enhanced training programmes and systemic reforms to embed inclusivity in teacher practices and institutional policies. This research provides a framework for scaling inclusive, technology-driven approaches in diverse educational settings.